The SIOPE strategic plan: A European cancer plan for children and adolescents. (June 2016) - Vassal, Gilles; Schrappe, Martin; Pritchard-Jones, Kathy; Arnold, Fréderic; Basset, Luisa; Biondi, Andrea; Bode, Gerlind; Eggert, Angelika; Hjorth, Lars; Kamerić, Lejla; Kamerić, Neira; Karner, Sabine; et al.
Highlights: A long-term sustainable Strategic Plan was defined and achieved a broad consensus. The European paediatric haematology-oncology community worked in close partnership. The Plan aims to increase the rate and quality of cure of paediatric cancers. Seven medical and scientific objectives have been set up. SIOPE is steering the Plan's implementation via specific programmes and platforms.